2022
DOI: 10.1002/brb3.2636
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of psychological cravings and anxiety in women compulsorily isolated for detoxification using autonomous sensory meridian response (ASMR)

Abstract: Objective To explore the effects of the autonomous sensory meridian response (ASMR) on the psychological cravings and anxiety of women compulsorily isolated for detoxification. Method Around 122 women were recruited in a female drug detoxification center. Except for the 12‐week training of ASMR, the experimental conditions of the experimental group ( n = 60) were the same as those of the control group ( n = 62). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Given the acceptability of both VR relaxation and ASMR to people experiencing mental health problems ( 8 , 18 , 19 , 39 ), there is a huge potential for the therapeutic and clinical applications of VR-based ASMR, which could use positive affirmations and coping techniques or guided meditation exercises, among other techniques. With meditation practices, gentle whispering could contribute to the experience of comfort and safety, while immersive VR environments could support individuals in focusing attention on the present moment ( 40 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the acceptability of both VR relaxation and ASMR to people experiencing mental health problems ( 8 , 18 , 19 , 39 ), there is a huge potential for the therapeutic and clinical applications of VR-based ASMR, which could use positive affirmations and coping techniques or guided meditation exercises, among other techniques. With meditation practices, gentle whispering could contribute to the experience of comfort and safety, while immersive VR environments could support individuals in focusing attention on the present moment ( 40 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…ASMR can have deeply relaxing and sedating effects while working as a distraction from negative thoughts. Research indicates it can provide temporary relief to anxiety, depression, insomnia, and chronic pain (17)(18)(19). A functional MRI study found that ASMR experience is significantly associated with brain areas involved in emotional arousal, satisfaction, and reward (20).…”
Section: Virtual Reality Relaxation and Autonomous Sensory Meridian R...mentioning
confidence: 99%
“…Although ASMR and autism share auditory sensitivity, there is no evidence supporting the association between ASMR and autism [45]. ASMR videos have been reported to alleviate symptoms of depression and anxiety [1,46].…”
Section: Introductionmentioning
confidence: 99%
“…ASMR is suggested to significantly Zhongliang Yu and Zhizhong Wang are with College of Integrated Circuits and Optoelectronic Chips, Shenzhen Technology University, Shenzhen, Guangdong 518118, China. increase the sleepiness [5] and sleep quality [6], and to decrease the state anxiety and attentional bias to a certain extent [7]. Therefore, many people watch ASMR videos or audios for relaxing, reducing stress and depression, restraining chronic pain, and promoting sleep [8,9].…”
Section: Introductionmentioning
confidence: 99%